PENGARUH MOTIVASI, ETOS KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL (PNS) PADA DINAS KEHUTANAN DAN PERKEBUNAN DAERAH KABUPATEN MOROWALI - Wahid, Ikhsan Abd. (Katalogis, 2016)
The objectives of this research are: 1) to determine and analyze the influence of motivation, work ethos, and work discipline on civil servants’ performance in The Department of Forestry and Plantations, Morowali Regency; 2) to determine and analyze the influence of motivation on civil servants’ performance; 3) to determine and analyze the influence of work ethos on civil servants’ performance; 4) to determine and analyze the influence of work discipline on civil servants’ performance. The type of this research is descriptive to verify relationships between variables and to answer the research questions by involving 35 respondents who are selected through census method.   Based on multiple linear regressions analysis results, it is found that: 1) motivation, work ethos, and discipline simultaneously influence civil servants’ performance positively and significantly; 2) motivation positively and significantly influences civil servants’ performance; 3) work ethos positively and significantly influences civil servants’ performance; 4) work discipline positively and significantly influences civil servants’ performance.